Parental Stress Scale: validation study with a Portuguese population of parents of children from 3 to 10 years old - Algarvio, Susana (2019)
The aim of this study was to validate the Parental Stress Scale (PSS) for Portuguese parents and to further investigate the scale's criterion-related validity. A two-stage stratified sample of the Portuguese population of parents, with children attending public preschools and primary schools, was obtained, totalizing 3842 parents of children between 3 and 10 years old. Parents completed a Parental Concerns Scale and the Portuguese version of the PSS. Results support the four-factor structure of the Portuguese version of the PSS. Higher levels of parental stress were reported by parents of boys, with lower educational levels; older, divorced or single parents; unemployed mothers; and with a higher number of children. Parental concerns and parental stress' comparative study reported very low correlations between the two constructs. This study supported evidence for the PSS' validity with a stratified sample of Portuguese parents of children between 3 and 10 years old. Moreover, our findings reported the scale's divergent validity with a Parental Concerns Scale. These results point to the importance of assessing both dimensions in family practice.